Becoming a Researcher: Navigating Messy Researcher Subjectivities. (1st July 2021) - Baker, Mandi
Abstract: In the process of doing research, I have experienced being an insider and outsider, belonging and exclusion, and feeling messy while trying to look tidy on multiple levels and, often, all at once. While these experiences sharpened my critical awareness, these seemingly dichotomous subjectivities often went unresolved. This article draws on post-structural theory to investigate the challenges to and value in embodying and performing multiple researcher subjectivities. I explore the tensions of "insider" subjectivities as a person who did research in an industry I was and still am personally involved. I consider the challenges to being human and having feelings as a researcher. I discuss the value of reflexive and creative ways of presenting research. This article concludes with insights from Foucault's approach to ethical care for the self that helped me make peace with the messiness of doing research and guides my beliefs in honoring research that resists traditional expectations.